Prediction of road pavement damage for local roads in Malaysia - Milad, Nasradeen Ali Khalifa (2016)
The high wheel loads of heavy trucks are a major source of pavement damage by causing fatigue, which leads to cracking and permanent deformation, which produces rutting. Malaysia, as one of the developing country has high level of road pavement damage. In addition to the cost of rehabilitating the pavement, serious safety issues occurs especially when the heavy trucks using U2/U3 roads, which not design to be use by heavy trucks. With aim to develop an analysis method and corresponding tool for local authorities to evaluate the impact of heavy trucks on local access roads, an observation was carried out to determine the characteristics of the trucks and operating conditions on local roads, from February, 2013 until July, 2014 at the Taman Kosas Utama Ampang Selangor and Taman Tas Kuantan Pahang (Malaysia). The mechanics of truck movement on the local access roads were studied to identify relationships between truck properties and road damage and to develop an appropriate method of data collection for these local roads. The WarpPLS is used as tool to develop the method and SPSS is used to examine the data and generate the model. Results indicated that regression relationships between road damage and other research factors been established with a coefficient of determination (R) at value of 0.71.